Conversational Health Bots for Telemedicine Services: Survey - Sura Mahmood Abdullah; Abbas Mohsin Al-bakry; Alaa Kadhem Farhan (Iraqi Journal for Computers and Informatics)
An increasing number of individuals take refuge in telemedicine systems for medical diagnosis and treatment due to their numerous benefits, including reduced healthcare costs, enhanced efficiency, and the ability to treat and prevent a wide range of physical and mental health problems. To improve the health status and clinical findings of older and underserved individuals, healthcare institutions have expanded telemedicine services, integrating them with advanced assisted living systems and environments. Conversational chatbots, or dialogue systems, are software tools designed to emulate human interaction via the Internet. These conversational bots can engage in natural conversations and can be merged into websites, mobile apps, and messaging platforms.